A hybrid exercise-based cardiac rehabilitation program is an effective strategy to improve muscle strength and functional exercise capacity in adults and older people with coronary artery disease - Marzuca-Nassr, Gabriel Nasri; Seron, Pamela; Román, Claudia; Gálvez, Manuel; Navarro, Rocío; Latin, Gonzalo; Marileo, Tania; Molina, Juan Pablo; Sepúlveda, Pablo; Oliveros, María José (Frontiers in Physiology, 2022)
Coronary heart disease is the most common cause of death worldwide. Standard cardiac rehabilitation (face-to-face sessions) has shown benefits in increasing muscle strength and functional exercise capacity in adults and older people. However, it is unknown whether hybrid cardiac rehabilitation (a first face-to-face phase + a second remote monitoring phase) will have similar benefits in adults versus older subjects. The aim of this study was to compare the effects of a hybrid exercise-based cardiac rehabilitation program on muscle strength and functional exercise capacity in “adult” versus “older” people with coronary artery disease. We hypothesized that a hybrid exercise-based cardiac rehabilitation program would improve muscle strength and functional exercise capacity, but the impact would be smaller in the older group than the adult individuals. This study is part of a larger project (The Hybrid Cardiac Rehabilitation Trial-HYCARET). We subjected 22 adult (<60 y) females and males (ADULT; n = 5/17 (f/m); 52 ± 5 y; 28.9 ± 3.4 kg·m-2) and 20 older (≥60 y) females and males (OLDER; n = 6/14 (f/m); 66 ± 4 y; 27.4 ± 3.9 kg·m-2) with coronary artery disease to 12 weeks of hybrid exercise-based cardiac rehabilitation program. Prior to and after 12 weeks of a hybrid exercise-based cardiac rehabilitation program, grip strength (handgrip), leg strength (chair stand test), and functional exercise capacity (6-minute walk test, 6MWT) were assessed. The hybrid exercise-based cardiac rehabilitation program resulted in a 9.4 ± 14.6% and a 6.2 ± 12.1% grip strength increase, a 14.4 ± 39.4% and a 28.9 ± 48.1% legs strength increase, and a 14.6 ± 26.4% and a 6.8 ± 14.0% functional exercise capacity improvement in ADULT and OLDER, respectively (p < 0.05) with no differences between groups. In conclusion, a hybrid exercise-based cardiac rehabilitation program could increase muscle strength and improve functional exercise capacity in adults and older people with coronary artery disease. More future studies comparing effectiveness among these age groups are needed to strengthen this conclusion.